Pengaruh Senam Anak Indonesia Hebat terhadap Tingkat Kebugaran Siswa Sekolah Dasar - Naswah Amalia Hartono; Kolekstus Oky Ristanto (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aimed to examine the extent to which the implementation of the Senam Anak Indonesia Hebat program contributes to improvements in physical fitness capacity among elementary school students. A quantitative approach was employed using a quasi-experimental non-equivalent control group design. The participants consisted of 66 fifth-grade students from SDN Baratajaya, divided into an experimental group (n = 35) and a control group (n = 31). The experimental group received the Senam Anak Indonesia Hebat intervention over two sessions, while the control group participated in regular Physical Education (PJOK) classes in accordance with the school curriculum. Physical fitness was assessed using the Tes Kebugaran Pelajar Nusantara (TKPN), which includes PACER, squat thrust, sit-up, and V-sit and reach components, scored through a proportional weighting system. Data analysis began with descriptive statistics, followed by the Shapiro–Wilk normality test and the Mann–Whitney U test to examine differences between groups. The findings indicated that the comparison between the experimental and control groups did not reveal a statistically significant difference (p = 0.621). Nevertheless, the experimental group demonstrated a greater tendency toward improvement in fitness scores compared to the control group. The limited duration of the intervention is presumed to have contributed to the absence of a statistically significant improvement in students’ physical fitness outcomes.